Effect of culture filtrates of Fusarium sporotrichioides on wheat callus culture - Valentina Yu. Stupko; Svetlana Yu. Lugovtsova; Nadezhda A. Neshumaeva (Аграрная наука Евро-Северо-Востока, 2025)
Cultivation of calli on media with culture filtrates (CF) of fungi of the genus Fusarium is used in breeding for the resistance to these pathogens of somaclonal lines of many plant species. The key is to determine the response of plant tissue culture to different concentrations (20 and 40 %) of CF. The dynamics of the growth and development parameters of spring soft wheat callus culture (CC) was assessed under simulating F. sporotrichioides infection in vitro in long-term cultivation (up to 119 days). Callusogenesis was induced in the culture of embryos on Murashige-Skoog (MS) medium with 2.4-D (1 mg/L for immature embryos, 4 mg/L for mature embryos). Calli were then cultured on media with the same levels of 2,4-D under different levels of CF (20 % and 40 %). The response of CC to CF was noticeable already by the 14th day of cultivation. Signs of necrosis were observed in 10–15 % of samples on media with CF. The proportion of calli with chlorophyll containing areas (CСA) at this period was half as much on media with CF compared to MS. By day 28, the medium with 20 % of CF had CCA quantity less than MS by 2-3 times, medium with 40 % of CF – had CCA quantity less by 5–7 times. The size of calli turned out to be less informative in the analysis of the response of CC to CF. After the 42nd day, media with CF showed the resumption of CC growth, slowing down of necrosis, and activation of chlorophyll synthesis. On the MS medium, the senescence of CC progressed, the frequency of calli necrosis increased. The same experiment but including passaging calli on the 14th day onto fresh media of the same composition did not reveal the increase in selective pressure. The results were either close to (CCA, necrosis) or higher (callus size) than those of the samples under continuous cultivation. Thus, the levels of CF used ensure the selection of wheat cell lines resistant to F. sporotrichiodes toxins within 28 days of cultivation. There is a potential to increase selection pressure.